Principle and technical analysis of loop drive - Jin, L.; Wu, S.; Li, Y.; Tang, W.; Yang, J.; Yin, S.; Chen, D.; Meng, X.; Li, Z.; Wang, Y.; Hou, Y.; Zhu, Y. (International Journal of Table Tennis Sciences, 2013)
researches on loop drive usually focus on describing the flying trajectory after the table tennis ball detaches from bat, but the theoretically explanation of loop drive is rarely reported. In this work, the tribology, mechanics, and space plane geometry deformation theories are adopted to investigate the motion features of loop drive, which are also employed to analyze the corresponding force distribution of bat. In brief, an integral loop drive motion consists of four movement stages and five friction pairs. The first stage is swinging the bat colliding with ball`s edge in a small angle. During this process, a slanting elastic concave-convex space deformation of rubber turns impact energy into relative tangential motion. Meanwhile, it forms a frictional normal load and with an elastic rolling normal surface structure, which frictionally carries and rebounds the ball to detach from bat with strong top-spin. This process is named as tangential hit. The second stage is the ball flying in a banana-ball trajectory. The third stage is collision process between ball and table, which also company with the ball`s slant-concave deformation and rolling over the table, and then the ball tosses out of the table in a decreasing angle with an irregular oscillation. The last one is a banana-ball track again. This work intends to figure out the intrinsic characteristics of loop drive, originates a tangential hit theory on loop drive. Furthermore, this work also intends to establish a loop drive technical system. In order to produce high quality loop drive, the player should swing bat to tangentially hit the ball in an appropriate small friction angle with a back-spinning-push track on the speedy time-space overlap area. Only by this way, the maximum frictional normal load can be obtained and get a loop drive of high quality.